Clinical Practice Guideline of Acute Respiratory Distress Syndrome - Cho, Young-Jae; Moon, Jae Young; Shin, Ein-Soon; Kim, Je Hyeong; Jung, Hoon; Park, So Young; Kim, Ho Cheol; Sim, Yun Su; Rhee, Chin Kook; Lim, Jaemin; Lee, Seok Jeong; Lee, Won-Yeon; et al. (Tuberculosis and respiratory diseases, 2016)
There is no well-stated practical guideline for mechanically ventilated patients with or without acute respiratory distress syndrome (ARDS). We generate strong (1) and weak (2) grade of recommendations based on high (A), moderate (B) and low (C) grade in the quality of evidence. In patients with ARDS, we recommend low tidal volume ventilation (1A) and prone position if it is not contraindicated (1B) to reduce their mortality. However, we did not support high-frequency oscillatory ventilation (1B) and inhaled nitric oxide (1A) as a standard treatment. We also suggest high positive end-expiratory pressure (2B), extracorporeal membrane oxygenation as a rescue therapy (2C), and neuromuscular blockage for 48 hours after starting mechanical ventilation (2B). The application of recruitment maneuver may reduce mortality (2B), however, the use of systemic steroids cannot reduce mortality (2B). In mechanically ventilated patients, we recommend light sedation (1B) and low tidal volume even without ARDS (1B) and suggest lung protective ventilation strategy during the operation to lower the incidence of lung complications including ARDS (2B). Early tracheostomy in mechanically ventilated patients can be performed only in limited patients (2A). In conclusion, of 12 recommendations, nine were in the management of ARDS, and three for mechanically ventilated patients.